Factors affecting milk constituents of Gir cows in an organized dairy herd (Indian Journal of Animal Production and Management, 2024)
The present experiment was conducted in an organized herd of lactating Gir cows during April, 2017  and October, 2018. Milk samples were collected from each quarter at monthly interval, checked for sub clinical mastitis by California Mastitis Test (CMT) as a routine practice and analyzed for milk constituents.  Total 1000 milk samples, negative for CMT were purposively included for the study to see the effect of  season (winter, summer and rainy), stage of lactation (early, mid and late) and parity (1st, 2nd-3rd and ≥4)  on milk constituents and to study association among different milk constituents. The overall milk fat, solid  not fat (SNF), protein, lactose and total solid (TS) percent were 4.111±0.020, 8.625±0.028, 3.180±0.011,  4.731±0.015 and 12.737±0.047%, respectively. There was significant (p≤0.05) effect of season on all  milk constituents (fat, SNF, protein and TS) except milk lactose. The concentrations of milk constituents  were significantly (p≤0.05) higher during rainy season as compared to winter season. Milk constituents  were affected significantly (p≤0.05) by the stage of lactation and parity of cows. Milk samples from early  stage of lactation comprised of significantly (p≤0.05) higher level of milk constituents than mid and late  lactation stages. Significantly (p≤0.05) higher level of milk constituents were observed in 1st parity cows  compared to other parities cows. There was significant (p≤0.001) positive correlation among different  milk constituents. On the basis of findings it can be concluded that season, stage of lactation and parity  affect milk constituents of Gir cows, while the positive association among milk constituents indicated that  improvement of one trait could improve the other traits.
Keywords: Gir cows; Lactation stage; Milk constituents; Parity; Season